Living Qur'an and Healing Practices: The Recitation of Syifā' Verses in Pesantren Pesulukan Agung, Tulungagung, Indonesia - Alfa Mardiyana; Eka Prasetiawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This research on the Living Qur'an examines the tradition of reading the Qur'an, which has developed from communal practices as a social response of specific communities to the Qur'an. The methodology employed is categorized as qualitative research, utilizing a Living Qur'an approach. Data collection is carried out through field research methods, employing triangulation techniques that integrate various data sources and interviews. The purpose of the study is to explore the interpretation of the Syifā' verses in the Qur'an and their application in therapy, as well as to address the challenges and responses of patients. The tradition of reciting Syifā’ verses at the Pesantren Pesulukan Agung in Tulungagung has been a longstanding mental health therapy practice, passed down through generations by a mursyīd (spiritual teacher). In practice, the recitation of Syifā’ verses is conducted by the mursyīd teacher or primary therapist in partnership with the patient. In this setting, the focus of mental health therapy at the Pesantren Pesulukan Agung transcends mere patient healing; it emphasizes achieving self-understanding, fostering human awareness, and cultivating a willingness to accept the decrees of Allah, which are regarded as essential components of the therapeutic process.